Dynamic Verb in Gorontalo Language - Mutiara Dyina Sari Laya (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
Local language is a language in region are still production in addition to indonesian as the firs languge of country” In relation with the position of Indonesian, local language has a function also as a tool of communication in a certain community. In addition a local language gives a contribution as a marker or the presence of a community. This follows the Mahsun's statement that “salah satu yang menjadi simbol atau lambang identitas suatu komunitas adalah bahasa Bangsa merupakan penanda komunitas (etnis) yang sangat penting” “one that has become a symbol or emblem identity of a community is a marker language of the community (ethical) is very important. Most of the Indonesian peoples are bilingual , which use Indonesian and regional languages, and most people in Indonesia use indonesian language as a second language and the local language as a first language. Gorontalo language or “Hulondalo” is a language of the people in Gorontalo. It is one of the province in sulawesi, Indonesia. There are many dialects in Gorontalo language, for example Suwawa, Tilamuta, Kuwandang, Paguyaman, Popayato and Bone dialects. This research will promote the Gorontalo language and morphosyntactic process of the verb.